2013
DOI: 10.1063/1.4826644
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a transverse magnetic field on 1/f noise in graphene

Abstract: The low frequency 1/f noise in graphene devices was studied in a transverse magnetic field of up to B = 14 T at temperatures T = 80 K and T = 285 K. The examined devices revealed a large physical magnetoresistance typical for graphene. At low magnetic fields (B < 2 T), the level of 1/f noise decreases with the magnetic field at both temperatures. The details of the 1/f noise response to the magnetic field depend on the gate voltage. However, in the high magnetic fields (B > 2 T), a strong increase of the noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…5d, V g 0.8 V). The larger detection limit compared to measurements at zero field is a result of both the reduced R H and a general increase in voltage noise in large background magnetic field, which is correlated with large longitudinal magnetoresistance and may also be attributed to charge fluctuations between localized and extended quantum Hall states 36,37 .…”
Section: Resultsmentioning
confidence: 99%
“…5d, V g 0.8 V). The larger detection limit compared to measurements at zero field is a result of both the reduced R H and a general increase in voltage noise in large background magnetic field, which is correlated with large longitudinal magnetoresistance and may also be attributed to charge fluctuations between localized and extended quantum Hall states 36,37 .…”
Section: Resultsmentioning
confidence: 99%
“…The physical effects discussed above might also explain the magnetic field dependence of the 1/f noise PSD observed at temperatures of 80 K and 285 K by Rumyantsev et al [68], since the quantum Hall effect in graphene persists up to room temperature in strong magnetic fields.…”
Section: Magnetic Field Dependence Of 1/ F Noisementioning
confidence: 87%
“…Amonst various types of noise, the 1/f α noise, which is also known as 'flicker' noise, is known to originate due to many processes occoring at atomic level. 11,[31][32][33][34][35][36][37][38] It has been reported that carbon nanotubes based cold cathode suffer from long-term current stability due to fast degradation rate, even though the cathode is competent to deliver high emission current density. 39 Recently, Hossain et.…”
Section: Introductionmentioning
confidence: 99%